A pentacyclic triterpenoid from Rubus sanctus - (:unkn) unknown (My University, 2004)
Rubus species are used for their analgesic and antidiabetic activities in traditional folk medicine. In this work, a triterpenic compound related with analgesic activity has been isolated. The compound is 2α,3α, 19α,24 tetrahydroxyurs-12-en-28-oic acid-28-O-β-glucopyranosyl ester.
Keywords: Rosaceae; Rubus sanctus; Triterpenoid